Preparation, characterization, and anticancer effects of an inclusion complex of coixol with β-cyclodextrin polymers - Xing-Chen Wang; Xin-Yu Shen; Lin Chen; Rong Wei; Ming-Yuan Wei; Cai-Hong Gu; Rong-Rong Xu; Sheng-Qing Ding; Bo Pan (Taylor & Francis Group, 2024)
AbstractContext Coix [Coix lacryma-jobi L. var. mayuen (Roman.) Stapf (Poaceae)], a crop of medicinal and edible significance, contains coixol, which has demonstrated anticancer properties. However, the limited solubility of coixol restricts its potential therapeutic applications.Objective This study prepared a water-soluble coixol-β-cyclodextrin polymer (CDP) inclusion compound and evaluated its anticancer effect.Materials and methods The coixol-CDP compound was synthesized through a solvent-stirring and freeze-drying technique. Its coixol content was quantified using HPLC, and its stability was tested under various conditions. The anticancer effects of the coixol-CDP compound (4.129, 8.259, 16.518, and 33.035 mg/L for 24, 48, and 72 h) on the proliferation of non-small cell lung cancer (NSCLC) A549 cells were evaluated using an MTT assay; cell morphology was examined by Hoechst nuclear staining; apoptosis and cell cycle was detected by flow cytometry; and the expression of apoptosis-related proteins was assessed by Western blots.Results The water-soluble coixol-CDP inclusion compound was successfully prepared with an inclusion ratio of 86.6% and an inclusion yield rate of 84.1%. The coixol content of the compound was 5.63% and the compound remained stable under various conditions. Compared to coixol alone, all 24, 48, and 72 h administrations with the coixol-CDP compound exhibited lower IC50 values (33.93 ± 2.28, 16.80 ± 1.46, and 6.93 ± 0.83 mg/L) in A549 cells; the compound also showed stronger regulatory effects on apoptosis-related proteins.Discussion and conclusions These findings offer a new perspective for the potential clinical application of Coix in NSCLC therapy and its future research.